Time to heal American medical educatio n from the turn of the century to the era of managed care - Ludmerer, Kenneth M.; American Council of Learned Societies (Oxford ; New York : Oxford University Press, 1999)
Kenneth M. Ludmerer describes the evolution of American medical educ ation from 1910 - when a muck-raking report on medical diploma mills sp urred the reform and expansion of medical schools - to the current era of managed care, when commercial interests once more have come to the f ore, compromising the training of the nation's future doctors. Ludmerer portrays the experience of learning medicine from the perspective of s tudents, house officers, faculty, administrators, and patients, and he traces the immense impact on academic medical centers of outside factor s such as World War II, the National Institutes of Health, private medi cal insurance, and Medicare and Medicaid.
Creating the system -- The American medical school between the world wars -- Undergraduate medical education -- The rise of graduate medica l education -- Teaching hospitals -- Academic medical centers and the p ublic -- World War II and medical education -- The ascendancy of resear ch -- The expansion of clinical service -- The maturation of graduate m edical education -- The forgotten medical student -- Medicare, medicaid , and medical education -- Medical education in an era of protest and c ivil rights -- Academic health centers under stress: external pressures -- Academic health centers under stress: internal dilemmas -- Internal malaise -- Medical education in an era of cost containment and managed care -- A second revolutionary period.
Includes bibliographical references (p. 401-494) and index.
Electronic text and image data.
Keywords: Medical education -- United States -- History -- 20th century